Produção de hidrocarbonetos através da síntese de Fischer-Tropsch utilizando catalisadores bimetálicos de Fe/Co dopados com K e Cu - Farias, Francisco Edson Mesquita (2012)
The reaction of Fischer-Tropsch synthesis has received great attention for its application in technology and science. This interest is associated with conversion of natural gas into high quality liquid products (gasoline and diesel) and high added value. In the present paper describes the methodology employed in the synthesis and characterization of bimetallic catalysts with high levels of the active phase of iron and cobalt, used in the synthesis of Fischer-Tropsch, supported on silica promoted with potassium and copper with different ratios on a molar basis. The use of iron catalysts used in the Fischer-Tropsch synthesis has been studied by many researchers, the results have shown that these have a satisfactory performance in the production of liquid fuels. However, studies have shown that cobalt catalysts are most effective in producing long-chain hydrocarbons and linear with respect to iron. However, the cobalt-based catalysts are more expensive compared to iron. A cost / benefit ratio has to be reached in the manufacture of catalysts which have such an optimization of production of synthetic fuels of high molecular weight inexpensively with the catalyst. The intention with this discussion, identify possible pathways for the development of more active and selective catalysts, varying the composition of the promoter structure for purposes of optimizing the distribution of products (diesel and grease). The reaction was conducted in a reactor bed of mud. The study followed an experimental planning factorial central square and the results were analyzed based on the methodology of the analysis of response surfaces. The effects of different operating conditions (temperature and pressure) and different concentrations of potassium and copper in the distribution of liquid based on the chromatograms were compared, average carbon number (Nn). Before the tests with the bimetallic catalysts (Fe / Co) doped with different concentrations of potassium and / or copper, it was a better relationship between the metals (K, Cu) for the synthesis of a more efficient catalyst (50Fe/50Co/12K/5Cu/139SiO2). Since the goal of this formulation bimetallic take advantage of possible synergistic effects between the two metals (Fe / Co) and its structural promoters.